The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21873/anticanres.11495
|View full text |Cite
|
Sign up to set email alerts
|

ME-143 Is Superior to Genistein in Suppression of WNT Signaling in Colon Cancer Cells

Abstract: ME-143 alone and in combination with 5FU and oxaliplatin effectively inhibits the WNT/β-catenin pathway in colorectal cancer cells of diverse genetic background. β-Catenin is directly involved in the mechanism of inhibition, and clinical studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Growing evidence indicates that dietary factors along with alteration in the gutactivator protein 1 microbiota can affect WNT-signaling. Genistein, a soy-derived isoflavone, for which clinical trial phase 1 and 2 has been completed in CRC, inactivates WNT-signaling by GSK3-β targeting [ 202 , 203 , 213 ]. Fisetin (3,7,3′,4′-tetrahydroxyflavone) is a dietary flavonoid that inhibits GSK3-β and activates β-catenin in melanoma cells [ 180 ].…”
Section: Wnt-targeted Therapiesmentioning
confidence: 99%
“…Growing evidence indicates that dietary factors along with alteration in the gutactivator protein 1 microbiota can affect WNT-signaling. Genistein, a soy-derived isoflavone, for which clinical trial phase 1 and 2 has been completed in CRC, inactivates WNT-signaling by GSK3-β targeting [ 202 , 203 , 213 ]. Fisetin (3,7,3′,4′-tetrahydroxyflavone) is a dietary flavonoid that inhibits GSK3-β and activates β-catenin in melanoma cells [ 180 ].…”
Section: Wnt-targeted Therapiesmentioning
confidence: 99%
“…It has been shown that genistein can suppress cell growth in colon cancer by decreasing the activity of the PI3K/Akt pathway [ 46 , 47 ]. Genistein has also been implicated in epigenetic regulation of Wnt pathway genes [ 48 ] and reduced colonic tumor growth [ 48 ], as well as inactivating Wnt-signaling by targeting GSK3-β [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reference genome and gene annotations of Xenopus laevis were downloaded from Xenbase ( xenbase.org , v10.1). RNA-Seq reads were aligned to the reference genome (v10.1, xenbase.org ) using STAR (2.5.2b, [ 49 ]). The total number of uniquely mapped reads was 13–19 million reads per sample (56 % of sequenced reads).…”
Section: Methods Detailsmentioning
confidence: 99%
“…However, it has exhibited contradictory performance in previous studies on colon cancer and the Wnt/β-catenin signaling pathway. Cellular-level experiments using RKO and DLD1 cell lines revealed that genistein alone cannot inhibit Wnt signaling ( 55 ), whereas another report demonstrated that genistein, as an inhibitor of the Wnt/β-catenin signaling pathway, can prevent the development of early colon cancer in animals ( 56 ).…”
Section: Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%